2002
DOI: 10.1046/j.1365-2273.2002.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Has the internet overtaken other traditional sources of health information? Questionnaire survey of patients attending ENT outpatient clinics

Abstract: The aim of this study was to find out whether patients attending ENT clinics obtain health information about their medical condition and to assess satisfaction with the sources of health information, including the internet. Three hundred and thirty patients attending ENT outpatient clinics at District General Hospitals in Wigan and Warrington during June 2001 were asked to complete detailed questionnaires. Fifty-seven per cent of patients attempted to obtain health information before their visit to the special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 7 publications
2
44
4
Order By: Relevance
“…Previous studies have shown that the internet is already an important source of health information for patients with ENT conditions [6,7]. A higher proportion of our study population had access to the internet (85%) when compared to these older studies.…”
Section: Comparison With Other Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies have shown that the internet is already an important source of health information for patients with ENT conditions [6,7]. A higher proportion of our study population had access to the internet (85%) when compared to these older studies.…”
Section: Comparison With Other Studiesmentioning
confidence: 75%
“…Rokade et al [7] report that 45% of their participant population had access to the internet but only 13% of these patients used the internet as a source of health information. In 2004, Tassone et al reported that 64% of their participant population had access to the internet but only 18% of these patients had searched the internet for health information.…”
Section: Introductionmentioning
confidence: 99%
“…A key 11 driver in the growth of the Internet has been the introduction of 12 Internet-enabled 'smartphones', and these devices are now 13 emerging as everyday platforms for accessing information and 14 managing daily routines; there are now an estimated 1.08 billion 15 smartphones globally, with 84% of users using their devices to 16 browse online, and 69% downloading applications [2]. 17 eHealth, and use of the Internet as a source of health 18 information, has been postulated to present a range of benefits 19 to the end-user, including supplementation of information 20 received from a health practitioner, the provision of anonymity 21 in health information-seeking, a means of information exchange 22 and community support, and empowerment in seeking help for, 23 and understanding, medical conditions [3].…”
mentioning
confidence: 99%
“…However, the exact level of disparity between the sexes is not yet clear. While Nicholas et al (2002) report 48.8% of users of NHS Direct Online were male, Rokade et al (2002) report a more modest proportion of male users. Clearly, future research is required.…”
Section: Internet-based Health Informationmentioning
confidence: 97%
“…For instance, in 2006-2007, 64% of Australian households had Internet access, and the percentage of Australians with Internet access has increased each year since 1998 (ABS 2007a). Furthermore, even those without Internet access at home may still be able to access online resources at work or at public venues such as libraries (Rokade et al 2002). Thus, while health information on the World Wide Web ('Web') may not be available to all Australians, it would be accessible to many Australians.…”
Section: Internet-based Health Informationmentioning
confidence: 99%